Effect of Solution Temperature on Controlled Potential Transport Properties of Polypyrrole Conducting/Electroactive Membranes - Ansari Khalkhali, Reza (Asian Journal of Chemistry, 2016)
This paper deals with the effect of the solution temperature on transport of potassium cation across polypyrrole conducting/electroactive polymer membranes doped with p-toluene sulfonate and odecyl benzene sulfonate as counterions. Potassium ion was employed as a probe for investigation of the effect of electrolyte temperature. Investigation was carried out in two different solution temperatures. It was found that polypyrrole electroactive membranes or free standing films can be applied successfully at elevated electrolyte temperatures without any important loss in their mechanical properties. Little improvement in ion flux (K+ ion) across the polypyrrole doped dodecyl benzene sulfonate membrane was observed at higher solution temperature, but in the case of polypyrrole doped p-toluene sulfonate some decrease influx of potassium ion was observed.